655 Next generation of agricultural work guidelines for youth. (1st September 2016) - Salzwedel, Marsha; Weichelt, Bryan; Lee, Barbara C
Abstract : Background: The North American Guidelines for Children's Agricultural Tasks (NAGCAT) were released in 1999 and Safety Guidelines for Hired Adolescent Farmworkers (SaGHAF) were later released by the National Children's Centre for Rural and Agricultural Health and Safety. Research has demonstrated these guidelines are effective in reducing injuries and now serve as the "gold standard" for assigning agricultural work to youth. Sixteen years after the launch of NAGCAT, there are shortcomings, including inaccurate/incomplete recommendations, new types of jobs, and some guidelines that should be retired. Currently, guidelines are available only in paper format. Today's farm parents prefer to access resources digitally and use mobile devices, so these guidelines need to be updated to fit with today's technology. Methods: An advisory team was formed to assist in gathering knowledge about the type of work youth perform on farms, how they are being injured, and to advise on content. A literature search provided scientific evidence to support advisors' recommendations related to child development and occupational safety. Agricultural safety experts were consulted for content and practicality of updated work guidelines. Technology experts were engaged to develop mobile-responsive materials. Results: This project creates a set of agricultural work guidelines for youth, ages 7–18, that are based upon previously developed and proven guidelines, are technologically injected, digitally accessible, responsive to emerging work methods and hazards, and culturally relevant with language translation options. Conclusions: The NAGCAT/SaGHAF resources are an effective tool in reducing childhood agricultural injuries, but in paper format, the distribution and application is limited. By updating these resources and creating new delivery systems, it increases the likelihood they will continue to be an effective resource for guiding the assignment of jobs to youth working in agriculture.